2006
DOI: 10.1111/j.1365-2230.2006.02223.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation of actinic keratoses subsequent to therapy with sorafenib, a multitargeted tyrosine-kinase inhibitor

Abstract: The Ras-Raf-MEK-ERK signalling pathway is frequently dysregulated in human malignancies, as is angiogenesis and the vascular endothelial growth factor receptor (VEGF/VEGFR) pathway. These kinases are therefore important anticancer targets. The novel, oral treatment sorafenib (BAY 43-9006), has been shown to be an inhibitor of VEGFR, Raf and platelet-derived growth factor in clinical trials against a variety of cancers, with the greatest activity to date observed in metastatic renal cancer. Although side-effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
6

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 6 publications
1
49
0
6
Order By: Relevance
“…Other dermatologic reactions include paronychia and some nail changes, abnormalities in hair growth, xerosis, hypersensitivity reactions, non-specific maculopapular rashes, stomatitis, mucositis and pruritus (9-11). One case report described the incidental development of inflammation of previously undetected actinic keratoses while on sorafenib therapy (12). We presently report the self-limited inflammatory flare-up of actinic keratoses during erlotinib treatment.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Other dermatologic reactions include paronychia and some nail changes, abnormalities in hair growth, xerosis, hypersensitivity reactions, non-specific maculopapular rashes, stomatitis, mucositis and pruritus (9-11). One case report described the incidental development of inflammation of previously undetected actinic keratoses while on sorafenib therapy (12). We presently report the self-limited inflammatory flare-up of actinic keratoses during erlotinib treatment.…”
Section: Introductionmentioning
confidence: 93%
“…Other conventional chemotherapeutic agents which have been associated with the inflammation of actinic keratosis include docetaxel, doxorubicin, capecitabine, pentostatin, sorafenib and the combination of dactinomycin, vincristine, dacarbazine and doxorubicin, cytarabine and 6-thioguanine (8,12,23,24). The mechanism by which these agents lead to this effect is unknown, although abnormal DNA synthesis and a form of radiation recall have been postulated (12).…”
Section: Actinic Keratoses and Squamous Cell Carcinomasmentioning
confidence: 99%
“…The most clinically significant of these toxicities, HFSR, has also been referred to as hand-foot syndrome (HFS) and palmar-plantar erythrodysesthesia [14,32], and has been shown to occur in anywhere from 9% to 62% of patients receiving sorafenib or sunitinib [1,22,[25][26][27]29]. A meta-analysis to study the incidence and risk of HFSR in patients enrolled in prospective clinical trials in which either sorafenib or sunitinib was examined as a single agent was performed using a random-effects or fixed-effects model based on the heterogeneity of the included studies [1,33].…”
Section: Clinical Features and Incidence Of Dermatologic Toxicities Amentioning
confidence: 99%
“…Recently, Lacouture et al [7] described 2 patients in whom treatment with sorafenib, a multitargeted TKI, resulted in inflammation of AKs, which in 1 case progressed to invasive SCC. The authors speculated that sorafenib might target the dysregulated Ras pathway found in SCC and, moreover, might inhibit vascular endothelial growth factor and platelet-derived growth factor receptor-β, both critical to SCC angiogenesis in invasiveness [7].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Lacouture et al [7] described 2 patients in whom treatment with sorafenib, a multitargeted TKI, resulted in inflammation of AKs, which in 1 case progressed to invasive SCC. The authors speculated that sorafenib might target the dysregulated Ras pathway found in SCC and, moreover, might inhibit vascular endothelial growth factor and platelet-derived growth factor receptor-β, both critical to SCC angiogenesis in invasiveness [7]. A similar observation was reported by Hong et al [8], who described the development of 3 invasive, well-differentiated SCCs in a female patient treated with a combination of sorafenib and tipifarnib (a farnesyltransferase inhibitor) for metastatic renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%